Participatory research with young people with special educational needs and disabilities: a reflective account. Issue 3 (4th May 2022) - Sharpe, Lesley; Coates, Janine; Mason, Carolynne
ABSTRACT: This paper responds to the calls for researchers to be more transparent about their processes of conducting participatory research with young people. Set within the context of a doctoral project that explores the inclusion of young people with SEND in the UK School Games framework, the paper highlights challenges and triumphs of researching alongside young people with SEND. Participants were aged between 11 and 18 and attended either a special school, a SEND unit within a mainstream secondary school or a mainstream college. The paper offers two contributions to the field, first is the novel methodology, which offers researchers and practitioners fresh approaches to engage young people in research. Second is three reflective vignettes that are positioned within the methodology and provide transparency and insight into the messy and confusing processes of informed consent, data co-construction and research dissemination within a participatory research framework.